Determination of the phenotypic age in residents of Mexico City: effect of accelerated ageing on lung function and structure. Issue 3 (25th August 2020) - Buendía-Roldan, Ivette; Fernández-Plata, Rosario; Valdes-Bartolo, Abigail; Mejia, Mayra; Jaramillo, Luis E.; Martínez-Briseño, David; Santiago-Ruiz, Armando; Tapia-Aguilar, Hugo; Gómez-Zamora, Brenda; Pardo, Annie; Selman, Moises
Introduction: Phenotypic age better represents age-related biological dysregulation than chronological age. Recently, a multisystem-based ageing measure, which integrates chronological age and nine biomarkers, was proposed. Methods: Phenotypic age was determined in 774 residents of Mexico City over 60 years old and without respiratory problems. We arbitrarily classified as "accelerated" ageing, those showing >4 years compared with their chronological age, and "slowed" ageing, those with <4 years compared with chronological age. Demographic risk factors were analysed with structured questionnaires. Lung structure was evaluated by high-resolution computed tomography and functional competence was analysed by forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ), diffusion capacity of carbon monoxide ( D LCO ), and the 6-minute walk test (6MWT). Results: Overall, 13% of this cohort showed accelerated ageing, which was corroborated with four independent biomarkers of ageing, 42% had normal ageing and 46% had slowed ageing. Risk factors associated with accelerated ageing were male sex (OR 4.4, 95% CI 2.4–7.9; p<0.01), diabetes mellitus (OR 9.7, 95% CI 5.5–17.2; p<0.01), and long-term sleep duration (OR 2.9 95% CI 1.34–6.35, p<0.01). Among smokers, there was a slight but significant association with the number of pack-years. Subjects with accelerated ageing showed decreased FVC (p<0.0001), FEV1 (p<0.0001), D LCO (p<0.02) and walking distance in the 6MWT (p=0.0001). Slowed-ageing subjects presented less frequently with emphysematous lesions compared with those with accelerated ageing. Conclusions: A small but significant proportion of residents of Mexico City age rapidly, which is associated with male sex, diabetes, and long-term sleep duration. They exhibit lower levels of lung function and develop emphysema more frequently. Systemic accelerated ageing results in decline of lung function and predisposes to emphysema compared with healthy ageing https://bit.ly/3fmeO82